Abundancia, biomasa y floración de Thalassia testudinum (Hydrocharitaceae) en el Caribe de Costa Rica - Nielsen-Muñoz, Vanessa; Cortés, Jorge (Revista de Biología Tropical, 2008)
Abundance, biomass and flowering of Thalassia testudinum (Hydrocharitaceae) in the Caribbean coast Costa Rica. Three Thalassia testudinum seagrass beds were studied at Cahuita National Park, from August 2003 to August 2006. Additionally, biomass samples of this species were collected at the Gandoca-Manzanillo National Wildlife Refuge, and data obtained from both localities in 1988 were compared with this study. The total average biomass within the substrate was more than double the biomass above ground. The average biomass for rhizomes was 310.90±72.59g/m2, 187.62±97.67g/m2 for roots and 67.90±84.40g/m2 for green leaves. The density, abundance and frequency of T. testudinum, showed peaks in January, May and September. The abundance of T. testudinum was highest in July, the rainiest month. In May, from 3000 short shoots, 95 (3.17%) had flower in 2004, 20 (0.67%) in 2005 and 7 (0.23%) in 2006. For both localities and every year of the study, the percentage of male flowers was greater than female flowers. In 2004, the flower sex ratio was two male to each female, but in 2005 and 2006 the proportion was four male to one female. Flowering was between April and June, with a peak in May, and fructification between May and August. T. testudinum flowering was correlated with the minimum tides of the year in the park. Rev. Biol. Trop. 56 (Suppl. 4): 175-189. Epub 2009 June 30.